PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT BPR PRISMA DANA MANADO - MAKALUAS, CHRISTIAN G.; Pio, Riane J.; Sumampouw, Harry J. (JURNAL ADMINISTRASI BISNIS (JAB), 2017)
Every company should be able to anticipate any changes that arise. Anticipation isintended so that the company can achieve its goals without any disruption and obstacles.Important things to note in the relationship is job satisfaction Because the level ofsatisfaction will be able to improve employee morale, so it can be concluded that therelationship between employees with the company into a reciprocal relationship. At PTBPR Prisma Dana Manado. Robbins (2001). "Job satisfaction is defined as a generalattitude of a person to his work. This definition contains a broad sense. In other words jobsatisfaction is a complex summation of a number of differentiated and discrete jobelements. "According to Robert L. Mathis and John H. Jackson Jimmy Sadeli and BayuPrawira (2001) "states that performance is basically what employees do or do not do." Inthis study the authors use is Quantitative approach. Research time is estimatedapproximately 1 month, researchers conducted research on PT. BPR Prisma DanaManado, the number of samples in this study are all populations to be studied thatamounted to about 30 people. In the results of this study Job satisfaction has a very stronginfluence in the creation of employee performance PT.BPR Prisma Dana Manadooptimally, the value of R (correlation) produced shows that the relationship between thetwo variables terebut very strong, it can be said that job satisfaction and employeeperformance are positively related meaning is the variable ability of job satisfaction inaffecting employee performance in PT.BPR Prisma Dana Manado is very big. In line withthe results of the research and the conclusions expressed, the researchers put forward somesuggestions as follows: For PT.BPR Prisma Dana Manado in order to maintain andimprove the effect of job satisfaction on performance by maintaining the existing aspects ofjob satisfaction and always supervise the performance of its employees.Keywords : : Job Satisfaction, Employee Performance.